STRATEGI PENGABDIAN MASYARAKAT UNTUK PENCEGAHAN STUNTING DI DESA SUGERKIDUL MELALUI PROGRAM “SEBANTING” - Ryan Bintang Satria; Wage Nur Iman; Maylafasya Rismawanti; Romli Rivaldi; Rahmat Supriyanto; Untung Untung; Achmad Soafianto Saputra; Royhansyah Saputra; Denok Risky Ayu Paramita (LPPM Universitas dr. Soebandi, 2025)
Stunting is a persistent nutritional issue that continues to pose a major challenge in Indonesia, particularly in East Java. Sugerkidul Village, Jelbuk District, is one of the areas in Jember Regency with a high numbers of stunting. This community service activity aims to improve the knowledge of the people of Sugerkidul Village regarding stunting and its influencing factors through community service activities under the name of “SEBANTING”, Sugerkidul Bebas Stunting. The activities carried out include socialization of PHBS (Healthy Living Behavior) and stunting, poster competitions, and the provision of stunting pocketbooks. Socialization was conducted involving students of SMPN 2 Jelbuk as the primary target. The results show significant increase in students' understanding after attending the socialization. The poster competition also successfully stimulated students' creativity in conveying messages about stunting prevention. The compiled stunting pocketbook is expected to be a source for the community to obtain accurate information about stunting. Overall, this community service activity has made a positive contribution to increasing public awareness in Sugerkidul Village about the importance of stunting prevention. However, continuous efforts involving various parties are needed to achieve a significant reduction in stunting rates.